Procamallanus (Spirocamallanus) anguillae sp. n. (Camallanidae) and some other nematodes from the Indonesian shortfin eel Anguilla bicolor in Thailand - Moravec, F; Taraschewski, H; Anantaphruti, M Thairungroj; Maipanich, W; Laoprasert, T (Parasitology research, 2006)
A new species of parasitic nematode, Procamallanus (Spirocamallanus) anguillae sp. n. (family Camallanidae), is described based on specimens recovered from the intestine of the Indonesian eel Anguilla bicolor McClelland (type host) from southern Thailand (type locality Phuket Island). It is characterized mainly by the presence of 10-13 spiral ridges in the buccal capsule, length of spicules (366-372 microm and 198-216 microm), presence of a gubernaculum, arrangement of caudal papillae, and by the broad female tail with a digit-like projection bearing two cuticular spikes. In addition, two species of larval nematodes, Physalopteridae gen. sp. and Anisakis cf. simplex (Rudolphi 1809), were recorded from A. bicolor. All species are briefly described and illustrated.
Keywords: Camallanina; Thajsko; Animals; Thailand; Nematoda; Anguilla; mikroskopie elektronová rastrovací; Female; mužské pohlaví; zvířata; hlístice; Male; Microscopy, Electron, Scanning; ženské pohlaví